Water scarcity in Tegucigalpa, Honduras: Is the Guacerique Subbasin being affected by climate variability and the drag of sediments? - Rodríguez Cruz, German Onil (2021)
[Introduction]: Located in the lower section of the subbasin of the Guacerique River (210 km2), the Los Laureles reservoir (10 million cubic meters (MCM)) supplies 30 % of the population in Tegucigalpa, Honduras. The reservoir faces some problems during the rainy season due to increased turbidity and color, while during the dry season the volume lowers and the water mixes with sediments, hindering treatment. [Objective]: The objective of this study was to evidence the affectation of the climate variability and the drag of sediments to the water network of the Guacerique subbasin, estimating the historical availability of water compared to the presence of the El Niño Southern Oscillation (ENSO) phenomenon and sediment drag. [Methodology]: Historical water balances (2001 to 2016) of the Guacerique subbasin were obtained, and the sediment load was calculated. [Results]: Historical water production of the Guacerique subbasin was 99.4 MCM. Water production was 73.4 MCM during ENSO, 103.8 MCM during the Niño/Neutral mixed year, 84.3 MCM during neutral years, 112.5 MCM during the Niña/Neutral mixed year, and 216.5 MCM during the Niño/Niña mixed year. The sediment contribution to the dam through the hydric network was 488.8 kg month-1. A total of 1.7 % of sediments came from the Mateo River, 2.5 % from the El Ocotal brook, and 7.5 % from the El Achiote brook. [Conclusions]: Using hydric balances, climate variability is confirmed to affect water volumes in the Guacerique subbasin. Due to the dragging of sediments in the Guacerique River, storage capacity is reduced, resulting in less water availability and scarcity in the reservoir.